Kinerja Ombudsman Perwakilan Maluku Utara dalam Mewujudkan Pelayanan Publik yang Prima Di Kota Ternate - Suleman, Sukur (Universitas Muhammadiyah Ponorogo, 2018)
This study aims to analyze the performance ofÂ North Maluku Representative Ombudsman as a supervisory body in realizing excellent public service in the city of Ternate. This study used a qualitative approach with emphasis on phenomenology. The data obtained from this research is through observation, in-depth interviews and documentation, and secondary data is document tracking. Data analysis technique is qualitative analysis with Milles and Huberman model that is, collecting data, data reduction, display data, conclusion and verification. The results showed that the performance of Ombudsman representative of North Maluku in Ternate City was quite good by looking at the process and stages of acceptance of reports submitted by the community or the Ombudsman's initiative, clarifying the report, field infestigation to convince the existing information, performing mediation actions against the complainant and reported , as well as on the stages of recommendations based on the mechanisms and or rules contained in Law No. 37 of 2008 on the Ombudsman of the Republic of Indonesia. North Maluku Ombudsman is also always working with related institutions and socialize about the functions, duties and authority of Ombudsman, and coordination in order to prevent maladministration practices so that the community can contribute actively and can support the existence of Ombudsman as an independent oversight institution to public service providers both government and private in Ternate City